Hubungan antara Tayangan Kuliner Korea di Media Sosial dengan Perilaku Konsumtif - Mohammad Jordan Febrian Gunawan; Anne Maryani (Bandung Conference Series: Communication Management, 2024)
Abstract. The emergence of new media has had a major impact on its users, from the reach of information to changes in lifestyle behavior. With the existence of new media, social media emerged where Korean cultural impressions became popular. The existence of the Tiktok application as a product of this new media makes people share information and create various content which we also call content creators. This culture is spread through entertainment, culinary, fashion, and cosmetic shows which makes the audience of Tiktok seem hypnotized by its content which causes consumptive behavior to emerge. This phenomenon will be studied on followers of the @hugryfever account using the theory of Goyette et al (2010), including intensity, content, and valance of opinion with the aim of knowing the relationship between Korean culinary impressions and consumptive behavior. This study uses quantitative methods and correlational research types. Collecting research data through online questionnaires to @hungryfever followers totaling 100 respondents using random sampling techniques. After processing data from respondents' answers, this study found a relationship between intensity, content, and valance of opinion with consumptive behavior. Abstrak. Munculnya media baru atau new media telah memberikan dampak yang besar bagi penggunanya mulai dari jangkauan informasi sampai dengan perubahan perilaku gaya hidup. Dengan adanya new media muncul media sosial yang dimana tayangan budaya korea menjadi populer. Adanya aplikasi Tiktok sebagai produk dari new media ini menjadikan orang-orang membagikan informasi serta membuat berbagai konten yang juga kita sebut sebagai conten creator. Budaya ini disebarkan melalui tayangan hiburan, kuliner, fashion, dan kosmetik yang membuat penonton dari Tiktok ini seperti terhipnotis oleh konten-kontennya yang menyebabkan munculnya perilaku konsumtif. Fenomena ini akan diteliti pada followers akun @hugryfever menggunakan teori dari Goyette et al (2010), diantarnya intensity ,content, dan valance of opinion dengan tujuan untuk mengetahui adanya hubungan antara tayangan kuliner korea dengan perilaku konsumtif. Penelitian ini menggunakan metode kuantitatif serta jenis penelitian korelasional. Pengumpulan data penelitian melalui kuisioner secara online kepada followers @hungryfever yang berjumlah 100 responden menggunakan teknik random sampling. Setelah melakukan pengolahan data dari jawaban responden penelitian ini menghasilkan hubungan antara intensity, content, dan valance of opinion dengan perilaku konsumtif